The research of the effect of computer and information literacy self-efficacy on the achievement of information literacy - Tuncer, Murat; Balcı, Kürşat (My University, 2013)
In this research, the relations between the information literacy self-efficacy and computer self-efficacy as well as the achievement of information literacy are examined. The scale of information literacy self-efficacy, computer self-efficacy and information literacy achievement test are applied to 783 teacher candidates receiving education at Faculty of Education in Fırat University. It is determined with the regression analysis how the achievement of information literacy self-efficacy, computer self-efficacy and information literacy affect each other; when the regression (beta) coefficients standardized as a result of the analysis are examined, it is observed that the computer self-efficacy has a positive effect on information literacy self-efficacy. Nonetheless, it is observed that the information literacy self-efficacy has no significant effect on the achievement of information literacy, and also the computer self-efficacy has no significant effect on the achievement of information literacy
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Information literacy self-efficacy; Computer self-efficacy; The achievement of information literacy; Teacher training; Regression analysis